Eph family co-expression patterns define unique clusters predictive of cancer phenotype. (December 2014) - Al-Ejeh, Fares; Offenhäuser, Carolin; Lim, Yi Chieh; Stringer, Brett W.; Day, Bryan W.; Boyd, Andrew W.
Abstract The Eph genes are the largest sub-family of receptor tyrosine kinases; however, it is most likely the least understood and the arena for many conflicting reports. In this tribute to Prof. Martin Lackmann and Prof. Tony Pawson, we utilized The Cancer Genome Atlas resources to shed new light on the understanding of this family. We found that mutation and expression analysis define two clusters of co-expressed Eph family genes that relate to aggressive phenotypes across multiple cancer types. Analysis of signal transduction pathways using reverse-phase protein arrays revealed a network of interactions, which associates cluster-specific Eph genes with epithelial–mesenchymal transition, metabolism, DNA-damage repair and apoptosis. Our findings support the role of the Eph family in modulating cancer progression and reveal distinct patterns of Eph expression, which correlate with disease outcome. These observations provide further rationale for seeking cancer therapies, which target the Eph/ephrin system.